Left ventricular free-wall rupture: an unusual and deadly complication after iodinated contrast medium exposure during primary percutaneous coronary intervention - Upadhyay, Amar Nath; Kumar, Barun; Jayant, Ashok Kumar (International Surgery Journal, 2019)
Acute left ventricular free-wall rupture (LVFWR) is a fatal mechanical complication that occurs in about 1-3% of acute myocardial infarction patients. Amongst, the iodinated contrast medium induced LVFWR is a very rare complication. Yet, it cannot be disregarded as the iodinated contrast medium is commonly used in contrast-enhanced imaging techniques. Here we have presented a rare case of iodinated contrast medium induced LVFWR after primary percutaneous coronary intervention. The patient’s LV angiogram was suggestive of contrast extravasation from LV into the pericardial cavity. A small rent in the inferior LV wall was sutured, and the repaired area was covered with glutaraldehyde treated autologous pericardial patch. Post-operative complication of heavy bleeding and acute kidney injury was managed by blood components transfusion and hemodialysis. In conclusion, the contrast medium induced LVFWR has infrequent and unpreventable nature with acute hemodynamic alterations hence, should be treated aggressively to prevent life-threatening complication.